High‐resolution characterization of a PACAP‐EGFP transgenic mouse model for mapping PACAP‐expressing neurons. Issue 18 (3rd June 2016) - Condro, Michael C.; Matynia, Anna; Foster, Nicholas N.; Ago, Yukio; Rajbhandari, Abha K.; Van, Christina; Jayaram, Bhavaani; Parikh, Sachin; Diep, Anna L.; Nguyen, Eileen; May, Victor; Dong, Hong‐Wei; et al.
ABSTRACT: Pituitary adenylate cyclase‐activating polypeptide (PACAP, gene name Adcyap1 ) regulates a wide variety of neurological and physiological functions, including metabolism and cognition, and plays roles in of multiple forms of stress. Because of its preferential expression in nerve fibers, it has often been difficult to trace and identify the endogenous sources of the peptide in specific populations of neurons. Here, we introduce a transgenic mouse line that harbors in its genome a bacterial artificial chromosome containing an enhanced green fluorescent protein (EGFP) expression cassette inserted upstream of the PACAP ATG translation initiation codon. Analysis of expression in brain sections of these mice using a GFP antibody reveals EGFP expression in distinct neuronal perikarya and dendritic arbors in several major brain regions previously reported to express PACAP from using a variety of approaches, including radioimmunoassay, in situ hybridization, and immunohistochemistry with and without colchicine. EGFP expression in neuronal perikarya was modulated in a manner similar to PACAP gene expression in motor neurons after peripheral axotomy in the ipsilateral facial motor nucleus in the brainstem, providing an example in which the transgene undergoes proper regulation in vivo. These mice and the high‐resolution map obtained are expected to be useful in understanding the anatomical patterns of PACAP expression and its plasticity in the mouse. J. Comp. Neurol. 524:3827–3848, 2016. © 2016 Wiley Periodicals, Inc. Abstract : Mapping the nervous system expression of neuropeptide PACAP has had challenges, which have led to some controversies in published reports. Here we employ a transgenic mouse in which EGFP is driven by the PACAP promoter sequence to compare its expression in the nervous system with that in previous reports for PACAP.